2018
DOI: 10.1177/2333392817748870
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Contraception and Pregnancy Intention In Medicaid Managed Care

Abstract: Context:Clinical guidelines recommend the documentation of pregnancy intention and family planning needs during primary care visits. Prior to the 2014 Medicaid expansion and release of these guidelines, the documentation practices of Medicaid managed care providers are unknown.Methods:We performed a chart review of 1054 Medicaid managed care visits of women aged 13 to 49 to explore client, provider, and visit characteristics associated with documentation of immediate or future plans for having children and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…46 As some Medi-Cal Managed Care participants have reported being assigned to unfamiliar primary care providers, whose offices may not be accessible by public transportation, 30 the state has commissioned an access assessment 47 that is currently underway. 48 Of further concern, few primary care providers routinely assess pregnancy intentions and contraceptive need 49 and even fewer primary care providers have been trained to place intrauterine or subdermal contraception; fewer than 20% of family physicians report routinely placing or removing intrauterine or subdermal contraceptives. 50 Additional barriers to providing family planning services in Medicaid Managed Care Organizations include churning in enrollment 51 and the costs to clinics of stocking IUDs and contraceptive implants for placement when needed.…”
Section: Limitationsmentioning
confidence: 99%
“…46 As some Medi-Cal Managed Care participants have reported being assigned to unfamiliar primary care providers, whose offices may not be accessible by public transportation, 30 the state has commissioned an access assessment 47 that is currently underway. 48 Of further concern, few primary care providers routinely assess pregnancy intentions and contraceptive need 49 and even fewer primary care providers have been trained to place intrauterine or subdermal contraception; fewer than 20% of family physicians report routinely placing or removing intrauterine or subdermal contraceptives. 50 Additional barriers to providing family planning services in Medicaid Managed Care Organizations include churning in enrollment 51 and the costs to clinics of stocking IUDs and contraceptive implants for placement when needed.…”
Section: Limitationsmentioning
confidence: 99%
“…Assessing PI in primary care aligns with patient-centered counseling, a key component of which is optimizing patients' decision making (Barry & Edgman-Levitan, 2012;Dehlendorf, Fox, Sobel, & Borrero, 2016). Numerous efforts have been made to develop standardized tools that 1) routinize and standardize the process of assessing primary care patients' PI (Allen, Hunter, Wood, & Beeson, 2017;Bellanca & Hunter, 2013;Bello, Adkins, Stulberg, & Rao, 2013;Callegari, Aiken, Dehlendorf, Cason, & Borrero, 2017), 2) can be integrated into the clinical record (Simons & Kohn, 2018;Thiel de Bocanegra, McKean, Darney, Saleeby, & Hulett, 2017), and 3) are able to inform surveillance of family planning service delivery on a population level (Gavin et al, 2014).…”
mentioning
confidence: 99%
“… 1 3 5 Studies are finding recurring barriers to pregnancy counselling conversations in rheumatology, including time limitations, lack of knowledge and resources of practitioners, and comfort with the topic. 5 These conversations are of higher priority in women with RMD as there is increased adverse outcomes are appreciated in pregnant women with RMD versus non-RMD pregnant women, likely related to uncontrolled disease state at time of conception and teratogenic medications. 1 Comparable rates of unintended pregnancy have been demonstrated in those with and without RMD, even further raising the priority of these discussions and education of patients as a part of regular rheumatology office visits.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing provider documentation and billing codes is one way, which researchers have estimated pregnancy counselling and contraception counselling. 5 Thiel de Bocanegra et al performed a review of 1054 Medicaid managed care visits of women aged 13–49, which demonstrated a presence of only ‘12% of charts had documentation of pregnancy intention and 59% documented contraceptive use or billing codes’. 5 This would suggest that very few discussions about pregnancy counselling and contraception are occurring during these visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation